Pérdida progresiva de la agudeza visual en paciente con diabetes mellitus. - Torres Bajaña, Alba Violeta (2020)
Diabetes mellitus is a long-term (chronic) disease in which the body cannot regulate the amount of sugar in the blood, leading to hyperglycemia. This disease is the main cause of many microvascular complications and ocular conditions that can lead to blindness as a result. In the course of this disease, the patient may lose his visual acuity, this being impossible to recover since its effects cause irreversible damage. Their vision is affected by the evolution they have over the years and their respective general and ophthalmological controls. The objective of this clinical case is to determine the cause of the progressive loss of visual acuity with the respective optometric assessment tests, which is the measurement of visual acuity from a distance (6 meters away) and from near (35 to 40 centimeters). As he did not show improvement in VA, he was referred to the ophthalmologist after the ophthalmological evaluation. The diagnosis of this clinical case is diabetic retinopathy, diabetic macular edema and cataract, for which an annual consultation with the ophthalmologist and the optometrist is essential.